NLRP3 inflammasome as a therapeutic target in autoimmune inner ear disease - Yuan, Vincent G.; Kullar, Peter; Xia, Anping; Santa Maria, Peter L. (Frontiers in Audiology and Otology, 2025)
Autoimmune inner ear disease (AIED) is a rare cause of bilateral, progressive sensorineural hearing loss (SNHL) that often responds to immunosuppressive therapy. Once considered primarily a T cell–driven condition, recent evidence underscores the importance of innate immunity, with the NLRP3 inflammasome emerging as a central mediator of cochlear inflammation and tissue injury. Caspase 1 is triggered by NLRP3 inflammasome assembly, resulting in the production of the proinflammatory cytokines IL-1β and IL-18 and the induction of pyroptotic cell death. Its presence in cochlear macrophages and supporting cells points to a pivotal role in non-infectious inflammation and progressive sensorineural damage. Preclinical models and emerging clinical data implicate NLRP3 in AIED pathogenesis and support targeting this pathway therapeutically. This review examines the immunological mechanisms linking innate and adaptive responses in AIED, evaluates current and emerging therapies targeting NLRP3, and outlines future research directions. Targeting the NLRP3 inflammasome holds promise for improving diagnosis and developing precision treatments for autoimmune inner ear disease.